2010
DOI: 10.1029/2009jd012371
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of high‐level clouds represented in a global cloud system–resolving model with CALIPSO/CloudSat and geostationary satellite observations

Abstract: [1] Vertical and horizontal distributions of high-level clouds (ice and snow) simulated in high-resolution global cloud system-resolving simulations by the Nonhydrostatic Icosahedral Atmospheric Model (NICAM) are compared with satellite observations. Ice and snow data in a 1 week experiment by the NICAM 3.5 km grid mesh global simulation initiated at 0000 UTC 25 December 2006 are used in this study. The vertical structure of ice and snow represented by NICAM was compared with Cloud-Aerosol Lidar and Infrared P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 58 publications
(66 reference statements)
2
30
0
Order By: Relevance
“…A likely explanation for the underestimation is that while CloudSat can not distinguish between cloud ice and snow, precipitating ice is diagnostic in many climate models and therefore does not contribute to IWP. This is typically not the case for high resolution ( x < 10 km) models (e.g., Inoue et al, 2010), that treat snow as a prognostic variable, meaning it can interact with cloudy and dry environment during sedimentation. The comparison between model cloud ice and snow with retrieved total ice (observation-to-model approach) still has limitations due to assumptions in the retrieval, e.g., particle size distribution.…”
Section: Introductionmentioning
confidence: 99%
“…A likely explanation for the underestimation is that while CloudSat can not distinguish between cloud ice and snow, precipitating ice is diagnostic in many climate models and therefore does not contribute to IWP. This is typically not the case for high resolution ( x < 10 km) models (e.g., Inoue et al, 2010), that treat snow as a prognostic variable, meaning it can interact with cloudy and dry environment during sedimentation. The comparison between model cloud ice and snow with retrieved total ice (observation-to-model approach) still has limitations due to assumptions in the retrieval, e.g., particle size distribution.…”
Section: Introductionmentioning
confidence: 99%
“…The cloud properties in the upper troposphere (UT) have been evaluated in comparison with satellite observations (e.g. Inoue et al, 2010;Kodama et al, 2012).…”
Section: Analysis Datamentioning
confidence: 99%
“…A global high-resolution simulation with a mesh size of approximately 3.5 km using the Nonhydrostatic Icosahedral Atmospheric Model (NICAM; Sato et al 2009;Tomita and Satoh 2004) showed realistic behavior of tropical cloud systems associated with diurnal to intra-seasonal variability Sato et al 2009;Inoue et al 2010). An interesting result from the NICAM simulations is that the behavior of the ISO/MJO bears some similarity with the observations, even as the mesh size is coarsened to approximately 7 and 14 km Masunaga et al 2008;Taniguchi et al 2010), although such resolutions are not generally used for nonhydrostatic models.…”
Section: Introductionmentioning
confidence: 99%